Clinical effect of high-flow revascularization in microsurgery combined with endoscopic endonasal surgery for skull base tumors with intracranial and extracranial involvement - Wang, Zhi-Qiang; Tong, Xiao-Guang (Frontiers in Surgery, 2023)
Background The objective of the study is to investigate the surgical methods and clinical effects of high-flow revascularization in microsurgery combined with endoscopic endonasal surgery for skull base tumors with intracranial and extracranial involvement. Methods The relationships between skull base tumors and internal carotid artery (ICA), tumor location and size, and the extent of tumor invasion were assessed. Preoperative CT perfusion (CTP), magnetic resonance (MR) perfusion-weighted imaging (PWI) (MR-PWI), and digital subtraction angiography (DSA) were performed to evaluate collateral circulation and brain tissue perfusion. Then craniotomy through the fronto-orbitozygomatic approach was performed, based on which four cases received extended middle skull base approach+Dolenc approach + Fukushima bypass type I, and six cases received extended middle skull base approach+Fukushima bypass type III. After surgery, DSA, CT angiogram (CTA), and CTP/PWI were performed to evaluate the patency of the reconstructed vessels and cerebral perfusion, and contrast-enhanced MRI to evaluate the degree of tumor resection. All patients were followed up for 6–12 months. Results Among the 10 cases investigated, gross total resection was achieved in 8 cases, subtotal resection in 1 case, and partial resection in 1 case, as confirmed by CT and enhanced MRI. The patency of revascularization vessels was observed using fluorescein angiography during the operation in all patients and via DSA and CTA postoperatively in nine patients. One patient underwent ventilator-assisted ventilation because of respiratory failure and failed to undergo DSA and CTA. Regarding postoperative complications, one patient developed watershed cerebral infarction on the operated side but no sequelae after drug treatment, three patients developed facial numbness, which improved after 3 months, and two patients experienced worsened diplopia. After 6 to 12 months of follow-up on the nine evaluable patients, the Glasgow Outcome Scale (GOS) was 4–5 after surgery. In addition, 6-month follow-up results showed that one patient with clival chondrosarcoma developed recurrence on contrast-enhanced MRI, while no relapse was observed in the other patients. Conclusion For skull base tumors with intracranial and extracranial invasion and involving the ICA, revascularization might improve the total resection rate and reduce the recurrence rate and risk of intraoperative bleeding and postoperative ischemia.